Theory of Constraints: A Literature Review - VAYVAY, ÖZALP; KALENDER, ZEYNEP TUĞÇE (ELSEVIER SCIENCE BV, 2014)
Theory of Constraints (TOC) is a management philosophy which is focused on the weakest ring(s) in the chain to improve the performance of systems. Companies, whether they are in the production or service sector should be more focused on understanding their own structure in terms of processes to survive in a global competition. In this situation, TOC becomes an important problem structuring and solving methodology which changes the way of thinking of managers. Since the TOC first put forth by Goldratt (1984) in his novel The Goal, the theory has drawn wide attention from practitioners and academic researchers. This study provides a review of the TOC evolution literature by its five era; the optimized product technology era, the goal era, the haystack syndrome era, the it's not luck era and the critical chain era. Our search at historical background and basic concepts of TOC aims to see how this philosophy evolves through time and how the main point of TOC researches changes. Crown Copyright (C) 2014 Published by Elsevier Ltd.
Keywords: Theory of constraints; Optimized production technology; The goal; The haystack syndrome; Critical chain project management; OPTIMIZED PRODUCTION TECHNOLOGY; METHODOLOGY; PERFORMANCE; PHILOSOPHY; OPT